PENGARUH ARUS PENGELASAN PADA BAJA ASTM SA 516 Gr70 TERHADAP KEKUATAN TARIK DAN KETANGGUHAN LAS SMAW DENGAN ELEKTRODA E7018 - Mohamad Faizal; Ali R Salam (Bina Teknika, 2018)
The strength of the weld is influenced by the arc voltage, the magnitude of the current, the speed of welding, the magnitude of the penetration and the electrical polarity. The determination of the magnitude of the current in metal grafting using arc welding affects the efficiency of the work and the weld material. Based on the existing problems, this research aims to determine the effect of low carbon steel welding current on tensile strength, toughness, hardness and micro structure to use SMAW with E7018 electrode using experimental research methodology using low alloy steel ASTM SA 516 gr 70 containing chemical element C = 0.16%, Si = 0.37%, Mn = 0.146%, S = 0.11%, Ni = 1%, Nb = 1%, Cr = 2%, Cu = 0.47%. Material welded with a variation of welding current 110 A, 130 A and 150 A using reverse polarity DC SMAW with E7018 electrode diameter of 3.2 mm. Specimens were tested for tensile strength, toughness, hardness and microstructure photographs with the highest tensile strength results in a variation of 130 A currents with an average of 546.83 MPa which increased by 21.77 MPa from raw materials. The highest yield strength at 130 A current variation with an average of 377.27 MPa which increased by 17.27 MPa from raw materials. The toughness in the highest welding area occurs in the 110 A current variation of an average of 1.85 Joule / mm2, it decreases 0.375% of the raw materials. The highest level of hardness occurs in the weld metal area with an average of 201.5 HVN of current variation of 150 A, this show in the micro structure of the grains are softer than the variations of other welding currents.